The Effects of Latarjet Reconstruction on Glenohumeral Instability in the Presence of Combined Bony Defects: A Cadaveric Model. Issue 3 (23rd March 2015) - Patel, Ronak M.; Walia, Piyush; Gottschalk, Lionel; Jones, Morgan H.; Fening, Stephen D.; Miniaci, Anthony
Objectives: Recurrent glenohumeral instability is often a result of underlying bony defects in the glenoid and/or humeral head. Anterior glenoid augmentation with a bone block (i.e. Latarjet) has been recommended for glenoid bone loss in the face of recurrent instability. However, no study has investigated the effect of Latarjet augmentation in the setting of both glenoid and humeral head defects (Hill-Sachs Defects (HSD)). The purpose of this study was to evaluate the stability achieved through a Latarjet procedure in the presence of combined bony defects. Our hypothesis was that Latarjet augmentation would increase shoulder stability for glenoid defects with small HSD, but have limited success in cases with large concomitant HSD. Methods: Eighteen fresh-frozen cadaveric specimens were tested at combinations of glenohumeral abduction (ABD) angles of 20°, 40°, and 60° and external rotation (ER) angles of 0°, 40°, and 80°. Each experiment applied a 50N medial load on the humerus to replicate the static load of soft tissues, and then simulated anterior dislocation by translating the glenoid in an anterior direction. Translational distance and medial-lateral displacement of the humeral head, along with horizontal reaction forces, were recorded for every trial. Specimens were tested in an intact condition (no defect), different combinations of defects, and with Latarjet augmentation. The Latarjet was performed for 20% and 30% glenoid defects by transferring the specimen's coracoid process anterior to the glenoid flush with the articulating surface. Results: Results are summarized in Fig. 1. The vertical axis represents the normalized distance to dislocation with respect to the values of the intact joint. The horizontal axis represents the varying sizes and combinations of bony defects. Latarjet augmentation improved stability for every combination of bony defects. At 20° ABD, 0°ER, and 20% glenoid defect size, the percentage of intact translation did not change with increasing HSD size, and the Latarjet augmentation increased percent intact translation to greater than 100 percent for all cases (Fig. 1A). However, at 60° ABD, 80° ER, and 20% glenoid defect size, increasing HSD size caused decreased stability, and Latarjet augmentation did not increase the percent intact translation to normal levels for HSD sizes greater than 30% (Fig. 1B). Conclusion: This is first study to investigate and quantify the effect of Latarjet reconstruction on anterior shoulder instability in the presence of combined humeral head and glenoid defects. Clinically, these results demonstrate that some degree of stability can be regained for combined bony Bankart and Hill-Sachs defects with a Latarjet procedure. However, for humeral defects larger than 30%, the HSD led to persistent instability in the abducted externally rotated position, even after the Latarjet procedure. Thus, directly addressing the humeral defect to restore the articular surface should be considered in these cases.